The various effects of Nigella sativa on multiple body systems in human and animals - Al-Juhaishi, Mohammed Abdulrazzaq Assi; Mohd Noor, Mohd Hezmee; Bachek, Noor Farhana; Ahmad, Hafandi; Haron, Abd Wahid; Mohd Yusoff, Md Sabri; Rajion, Mohamed Ali (Universiti Putra Malaysia Press, 2016)
Nigella sativa (Black seeds) has been recognized as one of the most popular herbs in many parts of the world for centuries. It was used in the world as folk medicine to cure different kinds of diseases. This plant has been considered as one of the main sources of nutrition and healthcare for humans as well as animals. It has been perceived as Kalonji; it is a southwest Asian plant that flowers annually. The seeds and oil of this plant have been used in food; in addition, it has a long history in the making of medicines. In addition to its being a model plant for better realization of gene and chromosome relationship, the plant species is also significant cytogenetically. Plant based system has not been absorbed fully for human health care despite the remarkable advancements in the field of pharmacology. Cumin, as one of the medicinal plants gifted to humans by nature, has a number of potential uses. It has been proved to be a useful herbal medicines that can be used for human health and therefore has been extensively studied and investigated to further discover the advantages of this plant.